Uncovering the Fecal Bacterial Communities of Sympatric Sika Deer (Cervus nippon) and Wapiti (Cervus canadensis) - Jiakuo Yan; Xiaoyang Wu; Xibao Wang; Yongquan Shang; Honghai Zhang (Animals, 2022)
Microbial symbiotic associations may be beneficial, neutral, or harmful to the host. Symbionts exploit the host space and nutrition or use hosts as carriers to spread to other environments. In order to investigate the fecal bacterial communities of wild sika deer (Cervus nippon) and wapiti (Cervus canadensis), this study aimed to sequence and explore the composition of, and similarity between, the fecal microbiota of sika deer and wapiti using high-throughput sequencing. The composition and relative abundance of fecal microbiota, alpha diversity, and differences in beta diversity between the two species were analyzed. We found that no pathogenic bacteria were present in large quantities in the hosts. The dominant bacterial phyla found in the two deer species were similar and included Firmicutes, Bacteroidetes, Proteobacteria, and Spirochaetes. Moreover, the deer also shared similar dominant genera, including the Rikenellaceae RC9 gut group, Ruminococcaceae_UCG-010, Ruminococcaceae_UCG-005, and Bacteroides. These results demonstrate that the sika deer and wapiti share a similar fecal microbiotal structure, probably due to their common diet and living environment, but there was some evidence of a difference at the species level. These analyses provide new insights into the health status of deer populations outside protected environments and offer a scientific framework for monitoring the health conditions of sika deer and wapiti.